Defect evolution and photoluminescence in anion-defective alumina single crystals exposed to high doses of gamma-rays. (February 2016) - Kortov, V.S.; Pustovarov, V.A.; Shtang, T.V.
Abstract: A method of luminescent UV and VUV spectroscopy was used to study the evolution of color centers in anion-defective alumina single crystals exposed to high doses of gamma-radiation. A sharp drop in the intensity of the emission bands and, therefore, the concentration of F + and F-centers associated with the formation of aggregate F2 -type centers was found. The aggregate centers create an additional emission band in the range of (1.8–2.8) eV. When the crystals are exposed to middle and high doses, the photoluminescence (PL) intensity is the highest in the emission band of F2 2+ -centers, which indicates a high concentration of the aggregates from singly charged oxygen vacancies (of F + -centers). When PL of the crystals exposed to high doses is excited with synchrotron radiation of the VUV range, a wide emission band in the red and near infrared (NIR) regions is registered. The centers related presumably to impurity defects, their aggregates and clusters consisting of several oxygen vacancies are responsible for this emission band. Highlights: PL of alumina exposed to high doses was measured under UV and VUV excitations. The emission of F + and F-centers decreases with a growing dose. New wide emission bands appear in the PL spectrum after irradiation. Oxygen divacancies are formed under high-dose irradiation of alumina crystals. High-dose exposure intensifies PL in the red–NIR spectral region.